Binding of quinine to plasma proteins in falciparum malaria. - Silamut, K; White, N; Looareesuwan, S; Warrell, D (1985)
Plasma protein binding of quinine was measured in 12 patients with cerebral malaria on the first and seventh day of treatment, and in 7 patients with uncomplicated falciparum malaria on admission and also one month later. Binding was significantly higher and therefore the proportion of free drug was lower in cerebral malaria patients (free: total quinine concentration; 7.2 +/- 3.5%, mean +/- SD, on admission; 7.4 +/- 5.3% on day 7) compared with uncomplicated malaria patients on admission (10.2 +/- 5.8%) or following recovery (11.0 +/- 5.5%, n = 6) P = 0.011. Binding was significantly correlated with the red cell/total concentration ratio r = 0.56, P less than 0.0001. The ratio of cerebrospinal fluid to free (unbound) plasma quinine was 0.55 +/- 0.33 which suggests that quinine does not freely cross the blood brain barrier. These findings are relevant to the interpretation of total plasma or serum concentration, and may explain the rarity of serious quinine toxicity in severe falciparum malaria.